2015
DOI: 10.1002/jee.20106
|View full text |Cite
|
Sign up to set email alerts
|

Engineers at Play: Games as Teaching Tools for Undergraduate Engineering Students

Abstract: Background Many students may not respond strongly to instruction that they do not perceive as engaging. One pedagogical approach to help engage students involves the use of games. Educational games can provide students with a motivating and stimulating environment while providing them with immediate feedback to promote learning.Purpose This systematic review examines research focused on the implementation of games to teach undergraduate engineering students; it summarizes prevailing features and cites examples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
144
0
15

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(163 citation statements)
references
References 22 publications
4
144
0
15
Order By: Relevance
“…A continuación se realiza un análisis de los elementos de los juegos (Bodnar et al, 2016) que están presentes en cada una de las experiencias de gamificación diseñadas (tabla 1). Tabla 1.…”
Section: Elementos De Los Juegosunclassified
See 1 more Smart Citation
“…A continuación se realiza un análisis de los elementos de los juegos (Bodnar et al, 2016) que están presentes en cada una de las experiencias de gamificación diseñadas (tabla 1). Tabla 1.…”
Section: Elementos De Los Juegosunclassified
“…Dichas técnicas consisten en el uso de elementos para el diseño de juegos en entornos que no son juegos (Deterding, 2015). Uno de los principales beneficios del uso de la gamificación en el contexto educativo es la motivación del estudiante en su proceso de aprendizaje (Bodnar, Anastasio, Enszer & Burkey, 2016).…”
Section: Introductionunclassified
“…It should be noted that there were marginal differences in the post survey results and design challenge scores, however; significant growth was evident across the three classes. The literature states that students who engage in learning material earlier in their schooling and interacting with engineering faculty will learn and retain that material more efficently 15,16 . Project-based courses are not only effective at enforcing and teaching various key concepts 13 , but have also demonstrated that students internalize and comprehend the concepts being taught.…”
Section: Innovation Prototyping Strategiesmentioning
confidence: 99%
“…Furthermore, the purpose behind using a zombie theme is that students are better able to construct new ideas when the ideas are relatable to existing knowledge 21 . Enhancing innovation, prototyping strategies, design and the design process through the use of prototyping is an effective measure 13,16,12,11 . This same measure could be applied to freshmen level courses and potentially enhance the freshmen biomedical engineering experience.…”
Section: Innovation Prototyping Strategiesmentioning
confidence: 99%
“…Game-like aspects within a course have been shown to improve student learning and attitudes towards the course in a meta-analysis of 62 articles 8 . On vSTEM, students are able to gain "imaginary experience points" by completing their homework assignments and by becoming certified to use new pieces of lab equipment.…”
Section: Gaming Aspectsmentioning
confidence: 99%